Evaluasi dampak model flipped classroom terhadap prestasi matematika - Darmasunu, I Made Arya Trybayu; Agung Gede Agung, Anak; Luh Erni Sulindawati, Ni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The Flipped Classroom model is widely promoted as an innovative solution for improving mathematics achievement. Yet, classroom implementations often reveal a different reality: promising designs do not always translate into measurable gains. This study re-examines that promise through a quasi-experimental Non-Equivalent Control Group Design involving 104 eighth-grade students at SMP Negeri 1 North Kuta. The intervention was implemented over [insert duration, e.g., eight weeks], comparing a flipped classroom approach with conventional instruction. Mathematics achievement was analyzed using ANCOVA, controlling for students’ learning motivation and teachers’ pedagogical competence. Although the experimental group obtained a higher mean score (72.66) than the control group (68.23), the difference was not statistically significant (Sig. 0.223 > 0.05) after covariates were accounted for. Furthermore, learning motivation and pedagogical competence did not function as significant covariates. These findings challenge the assumption that instructional innovation alone guarantees improved outcomes. Rather than demonstrating effectiveness, the results highlight the contextual and readiness-dependent nature of flipped learning implementation. The study suggests that without sufficient student readiness for independent learning, flipped classroom interventions may yield limited impact. Therefore, future implementations should prioritize gradual scaffolding strategies that cultivate autonomous learning habits before fully adopting the flipped model. By documenting a null result, this research contributes to a more balanced evidence base on educational innovation and underscores the importance of implementation conditions in interpreting intervention outcomes.